Exocrine Pancreas Involvement in Celiac Disease: A Review - Pezzilli, Raffaele (Recent Patents on Inflammation & Allergy Drug Discovery, 2014)
There are numerous studies in the literature regarding the involvement of intestinal as well as extra intestinal organs during the course of celiac disease, and there is accumulating evidence regarding the pancreatic changes caused by this pathology. Method: The literature on the relationship between celiac disease and pancreatic involvement has been extensively reviewed. Results: Exocrine pancreatic involvement regards both the function and the morphology of the exocrine pancreas, and superimposed or more severe clinical changes seem to be related to the nutritional disturbances caused by celiac disease or by the disease itself. Patients with celiac disease may also develop a chronic pancreatitis more frequently than in general population both the intestinal and the extraintestinal manifestations of celiac disease. Conclusions: Fecal elastase 1-determination in celiacs may be useful in detecting and curing exocrine pancreatic insufficiency especially in patients with a new diagnosis of celiac disease or in those with refractory diarrhea. Few patents on pancreatic extracts are also briefly described.
Keywords: chronic pancreatitis